2011
DOI: 10.1080/09658211.2010.546802
|View full text |Cite
|
Sign up to set email alerts
|

Alcohol intoxication and memory for events: A snapshot of alcohol myopia in a real-world drinking scenario

Abstract: Alcohol typically has a detrimental impact on memory across a variety of encoding and retrieval conditions (e.g., Mintzer, 2007; Ray & Bates, 2006). No research has addressed alcohol's effect on memory for lengthy and interactive events and little has tested alcohol's effect on free recall. In this study 94 participants were randomly assigned to alcohol, placebo, or control groups and consumed drinks in a bar-lab setting while interacting with a "bartender". Immediately afterwards all participants freely recal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

14
82
4

Year Published

2013
2013
2018
2018

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 57 publications
(100 citation statements)
references
References 25 publications
14
82
4
Order By: Relevance
“…Consequently, intoxicated participants should report and accurately remember less peripheral information compared to sober participants. Schrieber Compo et al (2011) found this pattern, whereby intoxicated participants remembered fewer accurate peripheral details about an interaction they had with a bartender. We did not replicate these findings, however.…”
Section: Discussionmentioning
confidence: 89%
See 3 more Smart Citations
“…Consequently, intoxicated participants should report and accurately remember less peripheral information compared to sober participants. Schrieber Compo et al (2011) found this pattern, whereby intoxicated participants remembered fewer accurate peripheral details about an interaction they had with a bartender. We did not replicate these findings, however.…”
Section: Discussionmentioning
confidence: 89%
“…Schreiber Compo et al further theorized that participants who were actually intoxicated did not have the cognitive resources to compensate, and thus, were less likely to report 'I don't know' and were comparatively less accurate overall. In another study, Schreiber Compo et al (2011) examined whether 'don't know' responses varied in relation to alcohol intoxication (mean BrAC 0.08% versus mean BrAC 0.01%) when participants recalled what happened during a staged theft; in this study, however, 'don't know responses' did not vary depending on alcohol condition.…”
mentioning
confidence: 83%
See 2 more Smart Citations
“…The method in the study by Hagsand et al [9] is a good example of the most commonly used experimental procedure employed in laboratories in the UK, USA and Sweden with respect to this new emerging research topic. Similar methods were employed in other studies in the field [10][11][12][13][14][15][16]. The approximately 15 published studies on alcohol and witness memory have overall found no negative impact of alcohol on witnesses' memory.…”
Section: Journal Of Drug Abuse 2471-853xmentioning
confidence: 89%